2021
DOI: 10.2478/raon-2020-0064
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral volume measured preoperatively by magnetic resonance imaging is related to survival in endometrial cancer

Abstract: BackgroundThe aim of the study was to determine if the endometrial tumor volume (TV) measured by magnetic resonance imaging (MRI-TV) is associated with survival in endometrial cancer and lymph nodes metastases (LN+).Patients and methodsWe evaluated the MRI imaging and records of 341 women with endometrial cancer and preoperative MRI from 2008 to 2018. The MRI-TV was calculated using the ellipsoid formula measuring three perpendicular tumor diameters. Tumor myometrial invasion was also analyzed.ResultsHigher MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In our opinion, it should be considered to implement the long-standing suggestions regarding the use of tumor dimensions in future updates of the FIGO EC guidelines. Based on our study results and in accordance with the above-mentioned evidence in the literature [ 20 , 21 , 22 , 23 , 24 ], it could be recommended to include a tumor diameter larger than 40 mm or tumor volume larger than 20 mL as additional criteria in the selection of patients for pelvic lymph node dissection. Tumor size may be measured via TVU or MRI, but MRI may have added value in the case of small tumors with doubtful findings on TVU or for more accurately measuring tumor size and detection of imaging signs of ≥pT1b disease.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In our opinion, it should be considered to implement the long-standing suggestions regarding the use of tumor dimensions in future updates of the FIGO EC guidelines. Based on our study results and in accordance with the above-mentioned evidence in the literature [ 20 , 21 , 22 , 23 , 24 ], it could be recommended to include a tumor diameter larger than 40 mm or tumor volume larger than 20 mL as additional criteria in the selection of patients for pelvic lymph node dissection. Tumor size may be measured via TVU or MRI, but MRI may have added value in the case of small tumors with doubtful findings on TVU or for more accurately measuring tumor size and detection of imaging signs of ≥pT1b disease.…”
Section: Discussionsupporting
confidence: 80%
“…They are associated with a poorer prognosis, and therefore lymphadenectomy is recommended in addition to hysterectomy in these cases [ 2 , 7 , 10 , 12 , 13 , 14 , 15 , 16 , 21 , 25 ]. Pelvic and para-aortic lymph node resection holds a risk of lymphocele and/or lower limb oedema [ 23 ]. The sentinel lymph node (SLN) has now become the new standard procedure as it may eliminate the need for extensive lymphadenectomy without risks of suboptimal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study published by Coronado et al 24 using the same formula, established 10 cm 3 or greater to classify the high‐risk group associated with poor prognosis in relation with survival and recurrence. Coronado et al 24 analyzed the tumor volume on preoperative MRI in a Spanish population similar to the population of the present study. Using a formula based on diameters, they showed that tumor volume is an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%